Лагерь призраков: [триллер для детей] / Р. Л. Стайн - Стайн Роберт Лоуренс (Ужастики, 2001)
Экземпляры: (20220321) / Инвентарный номер: 1695 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: С 76 / ББК: 84(7Сое)